Implementation of Project-Based Learning (PBL) to Enhance Conceptual Understanding of Zakat in Islamic Religious Education at The Elementary School Level - Rahayu, Tuti (Jurnal Keprofesian Guru Keagamaan, 2025)
This study aims to analyze the effectiveness of implementing the Project Based Learning (PjBL) model in improving student learning outcomes on the subject of zakat in Islamic Religious Education at the elementary school level. This study uses a Classroom Action Research (CAR) approach, which was carried out in several cycles with 17 fifth-grade students at SD Negeri 001 Arung Ayam as the subjects. Data were collected through observation, learning outcome tests, and documentation. The results showed a significant increase in student learning outcomes after the implementation of the PjBL model, with the average score increasing from 75.85 in cycle I to 85 in cycle II and 90 in cycle III. These findings indicate that the PjBL model is effective in increasing student engagement, motivation, and conceptual understanding of the concept of zakat. The implications of this study emphasize the importance of applying the project-based learning model in Islamic Religious Education to develop more contextual, active, and meaningful learning.